Holocene flood frequency reconstruction from speleothems in northern Spain. (1st November 2015) - González-Lemos, Saúl; Müller, Wolfgang; Pisonero, Jorge; Cheng, Hai; Edwards, R. Lawrence; Stoll, Heather M.
Abstract: Extreme precipitation events may cause flooding in the subsurface as well as surficial drainage networks, and these flood events may be preserved in the speleothem archive. We describe here a study of stalagmites from the Cueva Rosa, a system with a perennial cave stream in a lower active level and abundant speleothems in a fossil gallery 6–8 m above the active level. Several constrictions in the lower level act as bottlenecks at discharges of 8–11 m 3 /s during high discharge events, flooding both lower and upper galleries. Because the cave stream is the only efflux for the small surface watershed (1 km 2 ), it is possible to estimate the critical rainfall intensity rates and runoff required to flood the upper gallery. In the upper gallery, historical flooding is constrained by 14 C dates of wood fragments which register both a both post-bomb event and event at 420 yr BP. The latter event appears to coincide with deposition of thick mud deposit postdated by speleothem growth since 324 yr BP. A mid-Holocene (8.1–5.3 ka BP) speleothem from the upper gallery contains 26 detrital layers composed of clays and quartz grains evident in sectioned stalagmites and in Al content in LA-ICPMS analyses. The 9 most pronounced layers reach a thickness of 0.1–0.3 mm in the central growth axis. Petrography confirms that calcite crystal growth is continuous through these detrital layers and that they represent decantation events rather than hiatus in calcite deposition. In the mid-Holocene, large events have average recurrence of around 300 years, although large events are absent from the period from 7.3 to 6.3 ka and more frequent in the older and younger portions of the stalagmite. In the last four centuries, two major events have partially buried an actively growing stalagmite, showing that extreme precipitation events capable of flooding the upper gallery remain a persistent feature of the climate. Highlights: Cueva Rosa in NW Spain shows how cave sediments may record past flooding events. LA-ICPMS was used to confirm the occurrence of detrital layers inside stalagmites. U/Th and 14 C chronology allowed reconstruction of past flood frequency. Major flood events have ca. 311 year recurrence interval through the mid-Holocene.